Effects of early life stress and adolescent ethanol exposure on adult cognitive performance in the 5-choice serial reaction time task in Wistar male rats. - Boutros, Nathalie; Der-Avakian, Andre; Markou, Athina; Semenova, Svetlana (Psychopharmacology, 2017)
Rationale: Early life stress combined with heavy adolescent alcohol use predicts impaired neuropsychological functioning in adulthood. We investigated whether adolescent intermittent ethanol (AIE) exposure combined with neonatal maternal separation in rats altered attentional processes and impulsivity in adulthood. Methods: Male Wistar rat pups were exposed to maternal separation (postnatal days (PNDs) 1-14) and moderate AIE exposure (PNDs 28-57). Adult rats were tested in the five-choice serial reaction time task, which provides separate measures of attention, motor impulsivity, and compulsivity. Rats were tested under baseline conditions and in response to task manipulations that increased attentional load and impulsive behaviors, and after acute ethanol administration. Results: Short stimulus and short intertrial interval (ITI) durations disrupted attention while long ITI durations impaired impulsivity in all rats. Moderate- and high-dose ethanol challenges impaired attention in all rats. Rats exposed to maternal separation and/or AIE exposure had significantly decreased omissions than non-handled water-exposed rats at baseline and tended to retain this effect in response to task challenges (i.e., the shorter stimulus and ITI durations, longer test session) and ethanol challenges, indicating moderate improvement of attentional performance. Maternal separation significantly increased perseverative responses at baseline and in response to decreased stimulus duration challenge, suggesting increased compulsivity. Conclusions: Separate or combined exposure to early life stress and AIE exposure moderately disrupts some aspects of adult executive control functions (e.g., increased compulsivity) but improves others (e.g., increased attention). The relative intensity of either manipulation during neonatal and adolescent periods may influence the direction in which cognitive behaviors are affected in adulthood.